2015
DOI: 10.1080/02650533.2015.1073145
|View full text |Cite
|
Sign up to set email alerts
|

‘If I Feel Like This, How Does the Child Feel?’ Child Protection Workers, Supervision, Management and Organisational Responses to Parental Violence

Abstract: This study analysed workers' experiences of supervision following interactions with hostile and intimidating parents. This analysis examined management and organisational responses to worker stress, and assessed the adequacy of support that workers received. An online survey was designed to collect data on workers' experiences and free text responses were qualitatively analysed for references to the supervision they received in response to working with parents. 590 participants responded to the survey. 402 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
1
24
1
Order By: Relevance
“…Twenty-two of the included studies explored themes related to CWW experiences and/or consequences of organizational or management support (Samantrai, 1992;Landsman, 2001;Smith, 2005;Barak et al, 2006;Healy et al, 2009;Csiernik et al, 2010;Travis and Mor Barak, 2010;Augsberger et al, 2012;Lizano and Barak, 2012;Wu et al, 2013;Kruzich et al, 2014;Madden et al, 2014;Salloum et al, 2015;Baldschun et al, 2016;Dagan et al, 2016;Fernandes, 2016;Hunt et al, 2016;Littlechild et al, 2016;Antonopoulou et al, 2017;Griffiths and Royse, 2017;Hermon and Chahla, 2019). Healy et al (2009) conducted an international comparative study comprising of respondents from Australia, the United Kingdom, and Sweden.…”
Section: Social/organizational/management Workplace Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-two of the included studies explored themes related to CWW experiences and/or consequences of organizational or management support (Samantrai, 1992;Landsman, 2001;Smith, 2005;Barak et al, 2006;Healy et al, 2009;Csiernik et al, 2010;Travis and Mor Barak, 2010;Augsberger et al, 2012;Lizano and Barak, 2012;Wu et al, 2013;Kruzich et al, 2014;Madden et al, 2014;Salloum et al, 2015;Baldschun et al, 2016;Dagan et al, 2016;Fernandes, 2016;Hunt et al, 2016;Littlechild et al, 2016;Antonopoulou et al, 2017;Griffiths and Royse, 2017;Hermon and Chahla, 2019). Healy et al (2009) conducted an international comparative study comprising of respondents from Australia, the United Kingdom, and Sweden.…”
Section: Social/organizational/management Workplace Supportmentioning
confidence: 99%
“…They reported a positive relationship between workers perceived organizational support and experiences of a higher worklife balance. Both Hunt et al (2016) and Littlechild et al (2016) investigated the importance of organizational support among CWW facing violence and aggression from parents. In some of the included studies, participants reported different sets of safety measures installed in order to keep threats to their lives at bay.…”
Section: Social/organizational/management Workplace Supportmentioning
confidence: 99%
“…Workers are also victims of an unsupportive system. Staff turnover is indicative of unmanageable caseloads, complex and frightening work, lack of training, support and supervision (Hunt et al, 2015). It is not surprising that foster carers report inadequate everyday practice from workers who have to prioritise bureaucratic processes and life-threatening situations due to overwhelming workloads.…”
Section: Resultsmentioning
confidence: 97%
“…Child welfare workers (CWWs) in particular are disproportionately exposed to verbal and physical acts of violence due to their unique role and responsibilities (Newhill & Wexler, 1997; Shin, 2011). Such experiences may occur firsthand , such as physical and verbal violence or aggression from clients (Cornille & Meyers, 1999; Hunt et al, 2016; Newhill & Wexler, 1997; Robson et al, 2014; Rochelle & Buonanno, 2018), and home visits in unsafe neighborhoods or unsafe homes (Lamothe et al, 2018; Newhill & Wexler, 1997). These experiences can also occur secondhand , such as knowledge of violence or threats experienced by coworkers (Middleton & Potter, 2015; Newhill & Wexler, 1997), or exposure to stories and observations of clients’ suffering (Bride, 2007; Cornille & Meyers, 1999; Middleton & Potter, 2015).…”
Section: Introductionmentioning
confidence: 99%